2015
DOI: 10.1111/cjag.12067
|View full text |Cite
|
Sign up to set email alerts
|

Ex Ante Welfare Analysis of Technological Change: The Case of Nitrogen Efficient Maize for African Soils

Abstract: This study evaluates the potential impacts of the Improved Maize for African Soils (IMAS) project in two countries of Africa: Kenya and South Africa. The IMAS varieties offer significant yield advantages for regions where low or no fertilizer is used. The analysis uses spatial production data and household data to account for the level of fertilizer use in different agroecological zones of the country as well as different types of maize producing households. Results suggest that IMAS will deliver a total of US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The rapid development, dissemination, and adoption of drought‐tolerant maize has the potential to generate between US$362 million to US$590 million over a 7‐yr period, through both yield gains and an increase in yield stability (Kostandini et al, 2013). A similar ex ante study showed that low‐N‐tolerant maize has the potential to deliver a total of US$586 million in gross benefits, with US$136 million and US$100 million of benefits to producers in Kenya and South Africa (Kostandini et al, 2015). However the impact of stress‐tolerant maize on both total production and production variability within ESA is dependent on increased varietal turnover by the seed sector and adoption of new varieties by farmers (Cairns et al, 2013a).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The rapid development, dissemination, and adoption of drought‐tolerant maize has the potential to generate between US$362 million to US$590 million over a 7‐yr period, through both yield gains and an increase in yield stability (Kostandini et al, 2013). A similar ex ante study showed that low‐N‐tolerant maize has the potential to deliver a total of US$586 million in gross benefits, with US$136 million and US$100 million of benefits to producers in Kenya and South Africa (Kostandini et al, 2015). However the impact of stress‐tolerant maize on both total production and production variability within ESA is dependent on increased varietal turnover by the seed sector and adoption of new varieties by farmers (Cairns et al, 2013a).…”
Section: Discussionmentioning
confidence: 98%
“…The lowest realized genetic gain was observed under low‐N stress. Fertilizer use in SSA is very low compared with the rest of the world (less than 10 kg ha −1 compared with over 200 and 96 kg ha −1 in Asia and Europe, respectively), and fertilizer use in the region decreased between 1997 and 2007 (Kostandini et al, 2015). Many current commercial varieties have very low yields under low‐N stress, and because farm‐gate fertilizer prices are high in most of Africa relative to prices in other regions, N fertilizer application rates are likely to remain low for some years to come.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of potential pathways of change is common in ex ante appraisal (Alene et al, 2007;Kostandini et al, 2016;Mills, 1997). For example, the ADOPT tool is a method for predicting technology adoption, which is based on investigating potential users' perceptions of a technology's value and ease of use, as well as their personal or household characteristics that are assumed to influence the propensity to adopt (Kuehne et al, 2017).…”
Section: Towards Operationalisationmentioning
confidence: 99%
“…This result means that certification alone will not solve the challenge of improving farmer livelihoods in Uganda. The achievement of sustainable economic growth will require addressing not only marketing constraints but also production constraints such as the low use of improved varieties, the low intensity of fertiliser application and the lack of knowledge about appropriate agricultural practices (Dercon and Christiaensen, 2011;Asenso-Okyere and Jemaneh, 2012;Kostandini et al, 2015). Moreover, farm productivity will have to grow substantially to overcompensate the possible price squeeze of increased farm output and raise smallholder incomes at least for some time before Cochrane's treadmill sets in.…”
Section: Discussionmentioning
confidence: 99%